Impact of targeting the platelet-activating factor and its receptor in cancer treatment - Kimya Qaderi; Arvin Shahmoradi; Anita Thyagarajan; Ravi P. Sahu (Military Medical Research)
Abstract The lipid mediator platelet-activating factor (PAF) and its receptor (PAFR) signaling play critical roles in a wide range of physiological and pathophysiological conditions, including cancer growth and metastasis. The ability of PAFR to interact with other oncogenic signaling cascades makes it a promising target for cancer treatment. Moreover, numerous natural and synthetic compounds, characterized by diverse pharmacological activities such as anti-inflammatory and anti-tumor effects, have been explored for their potential as PAF and PAFR antagonists. In this review, we provide comprehensive evidence regarding the PAF/PAFR signaling pathway, highlighting the effectiveness of various classes of PAF and PAFR inhibitors and antagonists across multiple cancer models. Notably, the synergistic effects of PAF and PAFR antagonists in enhancing the efficacy of chemotherapy and radiation therapy in several experimental cancer models are also discussed. Overall, the synthesis of literature review indicates that targeting the PAF/PAFR axis represents a promising approach for cancer treatment and also exerts synergy with chemotherapy and radiation therapy.